Validity of Perceived Weight Gain in Women using Long-acting Reversible Contraception and Depot Medroxyprogesterone Acetate - NAULT, Ashley M. (2012)
OBJECTIVE: To evaluate perceived weight gain in women using contraception and determine the validity of self-reported weight gain. STUDY DESIGN: We analyzed data from new contraceptive method users who self-reported weight change at 3, 6, and 12-months after enrollment. We examined a subgroup of participants with objective weight measurements at baseline and 12-months to test the validity of self-reported weight gain. RESULTS: Thirty-four percent (1,407/4133) of participants perceived weight gain. Compared to copper intrauterine device users, implant users [relative risk (RR)=1.29, 95% confidence interval (CI), 1.10–1.51] and depot medroxyprogesterone acetate (DMPA) users [RR=1.37, 95% CI, 1.14–1.64] were more likely to report perceived weight gain. Women who perceived weight gain experienced mean weight gain of 10.3 pounds. The sensitivity and specificity of perceived weight gain were 74.6% and 84.4%, respectively. CONCLUSIONS: In most women, perceived weight gain represents true weight gain. Implant and DMPA users are more likely to perceive weight gain among contraception users.